2016
DOI: 10.1118/1.4967478
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of low‐contrast detectability between two CT reconstruction algorithms using voxel‐based 3D printed textured phantoms

Abstract: Purpose: To use novel voxel-based 3D printed textured phantoms in order to compare low-contrast detectability between two reconstruction algorithms, FBP (filtered-backprojection) and SAFIRE (sinogram affirmed iterative reconstruction) and determine what impact background texture (i.e., anatomical noise) has on estimating the dose reduction potential of SAFIRE. Methods: Liver volumes were segmented from 23 abdominal CT cases. The volumes were characterized in terms of texture features from gray-level co-occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 30 publications
3
67
0
Order By: Relevance
“…The resolution is expressed in dots per inch (dpi) or micrometers (lm) and assessed by comparing the dimensions of the produced physical phantom with the original dimensions provided to the printer. Among the papers used, 10 have assessed the resolution or accuracy of the printer by quantitative (numerical) comparison, [26][27][28][29][30][31][32][33][34][35] 10 by qualitative (figural) comparison, 22,[36][37][38][39][40][41][42][43][44] and 14 by both quantitative and qualitative comparison. 10,21,[45][46][47][48][49][50][51][52][53][54][55][56] Sixteen of the research articles do not include a verification of the printers' resolutions.…”
Section: A Characterization Of 3d-printed Phantom Spatial Accuracymentioning
confidence: 99%
“…The resolution is expressed in dots per inch (dpi) or micrometers (lm) and assessed by comparing the dimensions of the produced physical phantom with the original dimensions provided to the printer. Among the papers used, 10 have assessed the resolution or accuracy of the printer by quantitative (numerical) comparison, [26][27][28][29][30][31][32][33][34][35] 10 by qualitative (figural) comparison, 22,[36][37][38][39][40][41][42][43][44] and 14 by both quantitative and qualitative comparison. 10,21,[45][46][47][48][49][50][51][52][53][54][55][56] Sixteen of the research articles do not include a verification of the printers' resolutions.…”
Section: A Characterization Of 3d-printed Phantom Spatial Accuracymentioning
confidence: 99%
“…To compare CT reconstruction algorithms, Solomon et al developed a PolyJet 3D-printed liver tissue phantom based on a texture model with parameters derived from CT images. 16 They were able to achieve specific HU values using digital dithering of the available printer materials within a voxel, via custom software. The range of resulting HU values for the phantom was approximately 5 to 20 HU (at 120 kVp).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the morphological detail of tumors seen on CT scans may be preserved , while the heterogenous contrast differences of tumors may be reproduced with some degree of precision [11,20,21]. Similar to Bader et al [20], a graphical overview of the methods used are shown in Figure 1.…”
Section: D Printed Phantom Fabricationmentioning
confidence: 90%
“…These To prepare the volumes for 3D printing, the voxel Hounsfield unit (HU) values were normalized to range from 0 to 1. The new fractional intensity values were used to dictate the proportion of resin material that would be deposited in any given voxel [11]. To obtain the gray scale intensity gradients seen in CT scans, interpolation of each volume was necessary.…”
Section: D Printed Phantom Fabricationmentioning
confidence: 99%
See 1 more Smart Citation